2-Hydroxymethyl-1-methyl-5-nitroimidazole, one siderophore inhibitor, occludes quorum sensing in Pseudomonas aeruginosa - Yin, Lujun; Shen, Wang; Liu, Jun-Sheng; Jia, Ai-Qun (Frontiers in Cellular and Infection Microbiology, 2022)
Siderophore is necessary for the survival of microorganisms, and is inter-regulated with quorum sensing (QS) systems. It is related to growth, proliferation, virulence, and other bacterial social activities as a virulence factor. Thus, we speculated that QS system could be occluded by inhibiting siderophore production. 2-hydroxymethyl-1-methyl-5-nitroimidazole (HMMN), one siderophore inhibitor of Pseudomonas aeruginosa PAO1 (P. aeruginosa PAO1), was obtained by Chromeazurol S (CAS) method. We found HMMN inhibited siderophore production, and also influenced the biological effects of QS regulation, including biofilm formation and pyocyanin production. HMMN (150 μg/mL) inhibited siderophore production of P. aeruginosa PAO1 by 69.37%. In addition, HMMN could inhibit the pyocyanin production and biofilm formation, and could erase the formed biofilm of P. aeruginosa PAO1. HMMN (150 μg/mL) inhibited biofilm formation of P. aeruginosa PAO1 by 28.24%. The erasure rate of the formed biofilm reached 17.03%. Furthermore, HMMN (150 μg/mL) inhibited P. aeruginosa PAO1 pyocyanin production by 36.06%. While, positive control hordenine (500.0 μg/mL) reduced biofilm formation and pyocyanin production of P. aeruginosa PAO1 by 14.42% and 34.35%, respectively. The erasure rate of hordenine to the formed biofilm is 11.05% at 500 μg/mL. Quantitative real-time polymerase chain reaction (qRT-PCR) showed that HMMN not only down-regulate siderophore-related genes but also QS-related genes. Hordenine is as well. These results suggest that a siderophore inhibitor could be used as QSI to occlude QS system, and reduce virulence.